A plane wave model for direct simulation of reflection and transmission by discretely inhomogeneous plane parallel media. (July 2018) - Mackowski, Daniel; Ramezanpour, Bahareh
Highlights: An integral equation solution to the vector Helmholtz equation for plane parallel inhomogeneous layers is developed. The solution is fundamentally exact yet simple in comparison to volume integral methods applied to plane parallel systems. A discretized model for numerical calculations is developed and tested against benchmarks. The method can predict coherent backscattering and polarization opposition effects. Abstract: A formulation is developed for numerically solving the frequency domain Maxwell's equations in plane parallel layers of inhomogeneous media. As was done in a recent work [1], the plane parallel layer is modeled as an infinite square lattice of W  ×  W  ×  H unit cells, with W being a sample width of the layer and H the layer thickness. As opposed to the 3D volume integral/discrete dipole formulation, the derivation begins with a Fourier expansion of the electric field amplitude in the lateral plane, and leads to a coupled system of 1D ordinary differential equations in the depth direction of the layer. A 1D dyadic Green's function is derived for this system and used to construct a set of coupled 1D integral equations for the field expansion coefficients. The resulting mathematical formulation is considerably simpler and more compact than that derived, for the same system, using the discrete dipole approximation applied to the periodic plane lattice. Furthermore, the fundamental property variable appearing in the formulation is the Fourier transformed complex permittivity distribution in the unit cell, and the method obviates any need to define or calculate a dipole polarizability. Although designed primarily for random media calculations, the method is also capable of predicting the single scattering properties of individual particles; comparisons are presented to demonstrate that the method can accurately reproduce, at scattering angles not too close to 90°, the polarimetric scattering properties of single and multiple spheres. The derivation of the dyadic Green's function allows for an analytical preconditioning of the equations, and it is shown that this can result in significantly accelerated solution times when applied to densely-packed systems of particles. Calculation results demonstrate that the method, when applied to inhomogeneous media, can predict coherent backscattering and polarization opposition effects.